Penentuan Parameter Produksi Material Rem Ramah Lingkungan Untuk Aplikasi Kereta Api Menggunakan Serat Tandan Kosong Kelapa Sawit Sebagai Penguat - Syaeful A, Hilman; Pudja, IGN Wiratmaja; Triono, Agus (Jurnal Energi Dan Manufaktur; Vol 5 No 1 (2012): Oktober 2012, 2013)
Evaluation to determine production parameters of material for train brake that is environmentally friendly by using serat tandan kosong kelapa sawit (TKKS) as reinforcement was done by using extension evaluation method. The research was carried out with variations some of parameter productions or by making material such as pressure load, pressure time and temperatures. The samples then were tested based on criteria from the technical specification for composite brake from PT KAI. It is obtained from the testing that the best parameter productions are: Pressure 15 ton, pressuring time 40 minutes, and temperature is 200oC. The result from evaluation indicate that sample S14 as the the best sample that approach technical spesification from the PT. KAI
Keywords: rem komposit, tandan kosong kelapa sawit, extension evaluation